PBI‐type Polymers and Acidic Proton Conducting Ionic Liquids – Conductivity and Molecular Interactions. Issue 4 (10th August 2020) - Lin, J.; Korte, C.
Abstract: Proton conducting ionic liquids (PILs) are discussed as new electrolytes for the use as non‐aqueous electrolytes at operation temperatures above 100 °C. During fuel cell operation the presence of significant amounts of residual water is unavoidable. The highly Brønsted‐acidic PIL 2‐Sulfoethylmethylammonum triflate [2‐Sema][TfO] is able to perform fast proton exchange processes with H2 O, resulting from 1 H‐NMR and pulsed field gradient (PFG)/diffusion ordered spectroscopy (DOSY) self‐diffusion measurements. Proton conduction takes place by a vehicle mechanism via PIL cations or H3 O +, but also by a cooperative mechanism involving both species. Thus, highly Brønsted‐acidic PILs are promising candidates for the use as non‐aqueous electrolytes. To use [2‐Sema][TfO] as electrolyte in a proton electrolyte fuel cell (PEFC) it has to be immobilized in a host polymer. There is a (slow) uptake of the PIL by polybenzimidazole (PBI) up to a weight increase of ∼130%, due to a swelling process. A protonation of the basic imidazole moieties takes place. NMR analysis was applied to elucidate the molecular interactions between PBI, PIL, and residual water. Proton exchange, respectively an interaction between the polar groups and water can be observed in spectra, indicating a network of H‐bonds in doped PBI. Therefore, highly acidic PILs are promising candidates for the use as non‐aqueous electrolytes.